SISTEM INFORMASI PERIZINAN PADA KANTOR BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU (BPMPPT) KOTA JAMBI - Riswan - (JURNAL AKADEMIKA)
Web design and web programming are two terms that are very popular among web developers, web design is designing, web designing, web programming while is the person in charge to write the script for a site web programming. Both should complement each other to build a dynamic and interactive websites. Information technology, particularly through the internet media has grown so fast, especially with wireless or wireless media. Use of the Internet as a medium of information is very useful because it can be accessed by anyone. With a system that will be built in BPMPPT aims to provide information and data licensing service. Th is system was built with PHP programming language and uses MySQL as the database. With this system the user also can find instructions or procedures and licensing requirements in the conduct in this office, and also the user can know which companies are already listed in this BPMPPT office